Key Differences in Final Pathology Compared to Pre-Operative Clinical Diagnoses in the Liver Transplant Population: Implications for Quality Improvement. (28th October 2020) - Attaway, C C; Furth, E E; Tondon, R; Fortuna, D; Talwar, A
Abstract: Introduction/Objective: The pre-transplant clinical evaluation of patients with liver disease are critical components determining prognoses, eligibility and placement on the transplant waiting (eg. hepatocellular carcinoma (HCC) may decrease time on list), and surgical planning for the type of biliary anastomosis performed. For example, patients with Primary Sclerosing Cholangitis (PSC) are given direct liver to small bowel anastomosis, a type prone to ascending cholangitis, compared to duct to duct types in all other etiologies, and a clinical diagnoses of alcohol-induced cirrhosis impacts the patient's and family's psycho-social well-being. The goal of our study was to determine the frequency and types of differences in the clinical versus liver explant pathology diagnoses. Methods: A search for "liver explant" for all in-house cases between 7/15/2019 to 7/15/2018 and 1/1/2010 to 12/31/2010 identified 105 and 108 cases, respectively. For each case, pre-operative clinical diagnoses determined by the electronic medical record was compared to pathologic diagnosis. Cases with non-concordance were divided into two groups: 1. Concordant etiology but incidental malignancy identified in explant 2. Non-concordant etiology. Results: In the 2018–2019 group, of the 105 liver explants, 6 had concordant etiology but previously unknown HCC and 9 cases had non-concordant diagnoses. Similarly, the 2010 group, of the 108 liver explants, 6 had consistent etiology but previously unknown HCC and 8 cases non-concordant diagnoses. Of the total 17 non-concordant cases, 4 carried a pre-transplant diagnosis of PSC and were reversed to autoimmune hepatitis (2), chronic rejection, and primary biliary cholangitis on explant pathology and 3 carried a diagnosis of alcohol-induced cirrhosis and were reversed to portal tract venopathy, viral hepatitis, and alpha-1 antitrypsin. Conclusion: There are clinically significant discordances between pre-transplant and explant diagnoses with 6% incidental malignancies and 8% etiology changes. Of particular importance for anastomoses complications and psycho-social issues are patients with a pre-operative diagnoses of PSC or alcohol whose diagnosis was changed by pathology explant assessment, respectfully. Strategies to refine and improve pre-operative liver disease diagnoses particularly with regard to biliary and alcohol diagnoses will be explored.